Rare-earth tuned magnetism and magnetocaloric effects in double perovskites R2NiMnO6. (16th December 2021) - Ali, Anzar; Pasrija, Kanika; Sharma, Gyaneshwar; Kumar, Sanjeev; Singh, Yogesh
Abstract: We present a comprehensive experimental study of magnetization (2 < T < 300 K, 1 < H < 8 T) and magnetocaloric effect in double perovskite materials R 2 NiMnO6 with R = Pr, Nd, Sm, Gd, Tb, and Dy. While a paramagnetic to ferromagnetic transition, with TC in the range ∼ 100 − 200 K, is a common feature that can be attributed to the ordering of Mn 4+ and Ni 2+ magnetic moments, qualitatively distinct behavior depending on the choice of R is observed at low temperatures. These low-temperature anomalies in magnetization are also manifest in the change in magnetic entropy, −Δ S M, whose sign depends on the choice of R . In order to understand these results, we present theoretical analysis based on mean-field approximation and Monte Carlo simulations on a minimal spin model. The model correctly captures the key features of the experimental observations.